Crafting Strategic Maneuverability to Boost Business Performance - Hermas Kornelius; Innocentius Bernarto; Anton Wachidin Widjaja (ADI Publisher, 2020)
Few studies regarding strategic maneuverability are found in strategic management literature, and there were merely theoretical concepts with no empirical evidence to support the concepts. This study is an attempt to explore the concept and relationship between strategic maneuverability and company performance. The study uses a quantitative research method with respondents of 53 service companies in the oil and gas industry in Indonesia. The study's result supports that strategic maneuverability, with dimensions of organizational agility, flexibility, and responsiveness, has positive and significant effects on the company's performance in terms of financial, customer, internal process, and learning & growth. This study contributes to the literature in strategic management in general and the Theory of Maneuvers, particularly in two respects. First, it aims to operationalize and develop measures of strategic maneuverability. Second, to examine the relationship between strategic maneuverability and firm performance and providing empirical evidence.